Learning Styles: The Experience of the Medical School at the University of Nuevo León, Mexico - Cantú-Martínez, Pedro César (2018)
This article aims to clarify the learning style of students in the Medical School at the Autonomous University of Nuevo Leon (Mexico). In this research participated 333 students, men and women. They responded to a Honey-Alonso questionnaire to determine their learning styles. The results showed that the participants tend to possess a reflective and pragmatic learning style, which is consistent with the orientation of their professional preparation, and with other similar studies.